The disinfection effect of conventional disinfectants on Nosema bombycisG in different existence - SHI Lian-gen (浙江大学学报. 农业与生命科学版)
The disinfection effect of formaldehyde disinfectant (formalin) and chloric disinfectant (lime chloride) on Nosema bombycis of silkworm, Bombyx mori in the silkworm faeces, earth floor, silkworm larvae, pupa, moth body were studied. The results showed that formalin presented very powerful disinfection effect to Nosema spores in the above existence than lime chloride. However, both formalin and lime chloride didn't present a thorough paced disinfection to Nosema spores in the silkworm faeces (except formalin), earth floor, silkworm larvae, pupa, moth body under the conventional disinfection in sericulture.